Makna Filosofis Gelar Haji dalam Perspektif Sosial Budaya di Indonesia - Selfia Agustina; Rahmat Ramdhani; Ismail Ismail (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: : This study aims to examine the philosophical meaning of the title Haji from the socio-cultural perspective of Indonesian society. The title Haji not only represents success in fulfilling the fifth pillar of Islam, but also contains symbolic values influenced by local social and cultural constructions. This study uses a qualitative approach with a library study method, which focuses on various analyses of literature, scientific journals, Islamic books, and relevant anthropological and sociological works. The results of the study indicate that the title Haji has a philosophical meaning as a symbol of spiritual transformation, an existential journey towards piety, and a manifestation of total submission to God. In the Indonesian sociocultural context, this title is also understood as a marker of high social status, honor, and religious identity. Society places greater value on the holder of the title Haji, and forms moral and social expectations for their behavior. In addition, the meaning of this title is enriched through local traditions such as thanksgiving, the conferment of the title, and other symbolic honors. The research findings from this study are that the title Haji in Indonesia is not simply a sign of successful worship, but is a multidimensional symbol that reflects the combination of Islamic spiritual values and local cultural traditions. This shows that religious practices cannot be separated from the socio-cultural context that surrounds them.Keywords: The Hajj Title, Philosophical and Socio-Cultural Meaning.Abstrak: Penelitian ini bertujuan untuk mengkaji makna filosofis gelar Haji dalam perspektif sosial budaya mmasyarakat Indonesia. Gelar Haji tidak hanya merepresentasikan keberhasilan dalam menunaikan rukun Islam kelima, tetapi juga mengandung nilai-nilai simbolik yang dipengaruhi oleh konstruksi sosial dan budaya lokal. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka, yang berfokus pada analisis berbagai literatur, jurnal ilmiah, buku-buku keislaman, serta karyakarya antropologi dan sosiologi yang relevan. Hasil kajian menunjukkan bahwa gelar Haji memiliki makna filosofis sebagai simbol transformasi spiritual, perjalanan eksistensial menuju kesalehan, serta wujud kepasrahan total kepada Tuhan. Dalam konteks sosial budaya Indonesia, gelar ini juga dipahami sebagai penanda status sosial, kehormatan, dan identitas keagamaan yang tinggi. Mmasyarakat memberi nilai lebih kepada pemilik gelar Haji, serta membentuk ekspektasi moral dan sosial terhadap perilaku mereka. Selain itu, makna gelar ini diperkaya melalui tradisi-tradisi lokal seperti selamatan, penyematan gelar, dan penghormatan simbolik lainnya. Hasil penelitian dari studi ini adalah bahwa gelar Haji di Indonesia bukan sekadar tanda keberhasilan ibadah, tetapi merupakan simbol multidimensional yang mencerminkan perpaduan antara nilai-nilai spiritual Islam dan tradisi budaya lokal. Hal ini menunjukkan bahwa praktik keagamaan tidak dapat dilepaskan dari konteks sosial budaya yang melingkupinya.Kata Kunci: Gelar Haji, Makna Filosofis, Sosial Budaya